1998
DOI: 10.1086/514675
|View full text |Cite
|
Sign up to set email alerts
|

High‐Resolution Computed Tomography for the Diagnosis of Community‐Acquired Pneumonia

Abstract: We compared high-resolution computed tomography (HRCT) with chest radiography (CR) to determine if there is any advantage to using HRCT in the diagnosis of community-acquired pneumonia (CAP). Simultaneously obtained chest radiographs were compared with HRCT scans for 47 patients with clinical symptoms and signs suspicious for CAP, HRCT identified all 18 CAP cases (38.3%) apparent on radiographs as well as eight additional cases (i.e., 55.3%); P = .004. The corresponding figures for bilateral involvement were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
169
5
14

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(190 citation statements)
references
References 34 publications
2
169
5
14
Order By: Relevance
“…15,16 Our study does not reproduce these findings, with pneumonia being diagnosed as often despite increased utilization in CT. With increases in the number of nonspecific diagnoses and no improvements in clinically significant diagnoses such as PE and pneumonia among patients presenting with CC symptoms, increased utilization seems to provide little to add in the diagnostic work-up and certainly is not altering treatment in the setting of inappropriate ordering. Furthermore, with the escalating rates of CT utilization, a high number of clinically significant incidental findings have been reported, 6 which has led some physicians to argue that CT is useful in patients even when clinical suspicion of more concerning diagnoses (eg, PE) is high.…”
Section: Discussioncontrasting
confidence: 59%
“…15,16 Our study does not reproduce these findings, with pneumonia being diagnosed as often despite increased utilization in CT. With increases in the number of nonspecific diagnoses and no improvements in clinically significant diagnoses such as PE and pneumonia among patients presenting with CC symptoms, increased utilization seems to provide little to add in the diagnostic work-up and certainly is not altering treatment in the setting of inappropriate ordering. Furthermore, with the escalating rates of CT utilization, a high number of clinically significant incidental findings have been reported, 6 which has led some physicians to argue that CT is useful in patients even when clinical suspicion of more concerning diagnoses (eg, PE) is high.…”
Section: Discussioncontrasting
confidence: 59%
“…Furthermore, the percentage of false-negative CXR of this study concerning diagnosis of pneumonia is consistent with literature data. 28 Syrjala et al 28 comparing chest CT with CXR ability in the diagnosis of pneumonia, found 8 (30.8%) negative CXR cases out of 26 confirmed pneumonias. Another limitation of our study is that only one experienced operator performed all LUS, and it is reasonable to hypothesize that similar results cannot be immediately achieved by less experienced operators.…”
Section: Discussionmentioning
confidence: 99%
“…We think that the definition of asymptomatic infection should be reserved to the culture or PCR-positive patients without symptoms who have either seroconversion of antibodies or any lung infiltrate at thorax HRCT consistent with pneumonia-since it has been reported that HRCT has greater sensitivity than Chest X-Ray in diagnosing pneumonia [29,30].…”
Section: Discussionmentioning
confidence: 99%